2019
DOI: 10.1111/cge.13508
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular diagnosis of non‐phosphomannomutase 2 N‐linked congenital disorders of glycosylation in Spain

Abstract: The congenital disorders of glycosylation (CDG) are defects in glycoprotein and glycolipid glycan synthesis and attachment. They affect multiple organ/systems, but non‐specific symptoms render the diagnosis of the different CDG very challenging. Phosphomannomutase 2 (PMM2)‐CDG is the most common CDG, but advances in genetic analysis have shown others to occur more commonly than previously thought. The present work reports the clinical and mutational spectrum of 25 non‐PMM2 CDG patients. The most common clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 23 publications
2
29
1
Order By: Relevance
“…Literature review identified 14 articles published from 2005 to 2019 with individuals with ARCL2A or WSS due to deleterious variants in ATP6V0A2 (Medrano et al, 2019: Karacan et al, 2019; Beyens et al, 2019; Kariminejad et al, 2017; Ritelli et al, 2014; Bahena‐Bahena et al, 2014; Gardeitchik et al, 2014; Greally et al, 2014; Fischer et al, 2012; Hucthagowder et al, 2009; Kornak et al, 2008; Mohamed et al, 2011; Morava et al, 2005; Tantcheva‐Poor et al, 2012). A total of 70 affected individuals from 65 families, including ours, were found (Tables S1–S4).…”
Section: Resultsmentioning
confidence: 99%
“…Literature review identified 14 articles published from 2005 to 2019 with individuals with ARCL2A or WSS due to deleterious variants in ATP6V0A2 (Medrano et al, 2019: Karacan et al, 2019; Beyens et al, 2019; Kariminejad et al, 2017; Ritelli et al, 2014; Bahena‐Bahena et al, 2014; Gardeitchik et al, 2014; Greally et al, 2014; Fischer et al, 2012; Hucthagowder et al, 2009; Kornak et al, 2008; Mohamed et al, 2011; Morava et al, 2005; Tantcheva‐Poor et al, 2012). A total of 70 affected individuals from 65 families, including ours, were found (Tables S1–S4).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, CCDC115-CDG (MIM: #616828) and MPI-CDG (MIM: #602579) have especially severe liver disease [7]. CCDC115-CDG presents with a Wilson disease-like phenotype with hepatosplenomegaly, increased serum aminotransferases, neonatal jaundice, early cirrhosis, and increased liver copper concentration [8][9][10]; other CDG involved with Golgi membrane trafficking such as TMEM199-CDG can also present with similar Wilsonian features [11,12]. MPI-CDG tends to present with severe liver dysfunction and rapidly progressive (sometimes congenital) fibrosis [7,13], although asymptomatic adults have been reported [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…At least 38 genetically confirmed patients (from 26 families) have been reported [ 1 19 ]. The frequency and the prevalence of the disease are not known.…”
Section: Disease Characteristicsmentioning
confidence: 99%